Implementation Of AR and VR Through Google Expeditions In Social Studies Learning In Junior High School - Dara Rizkita Amelia; Indri Dwi Lestari; Wahyunengsih (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
AR and VR are forms of technology that present a more engaging way of learning, making students feel genuinely involved in the subject matter. Especially in social studies learning at the junior high school level, by bringing digital elements into the real environment, as if the two were one and could be seen or touched directly. At the same time, VR creates a three-dimensional virtual environment in which AR and VR can be explored in real time using devices such as Oculus glasses. This study aims to examine the implementation of AR and VR-based Google Expeditions in social studies learning and to determine the extent to which this technology can encourage students to think critically about social issues. In addition, this study examines the effectiveness and problems arising from the application of the technology. The approach used in this study is qualitative, with data collected through the analysis of Scientific Articles. The results of this study indicate that AR and VR technology are pretty helpful in facilitating insight and understanding, thereby deepening the material. However, the teachers still have to deal with issues like inadequate technical assistance and training, however. Therefore, for the implementation of this technology in the educational process to function smoothly and sustainably, suitable strategies and adequate education are required.